An Analysis of Character Building Portrayed in The Wild Robot Movie by Chris Sanders - Badrut Tamam; Linta Wafdan Hidayah; Jaftiyatur Rohaniyah (Penerbit Hellow Pustaka, 2025)
This research explores the character building portrayed in The Wild Robot movie by Chris Sanders, focusing on the transformation of the main character, Roz, from an emotionless robot into a figure full of empathy, responsibility, and leadership. The purpose of this study is to identify the types of character values presented in the movie and to analyze the internal and external factors that contribute to Roz’s character development. The research applies a descriptive qualitative method, using observation and documentation as the primary data collection techniques. The analysis is supported by Charles Sanders Peirce's semiotic theory and character education frameworks. The findings reveal that Roz demonstrates key character values such as empathy, compassion, adaptability, leadership, courage, and sacrifice. These values are shaped by both internal factors—such as cognitive ability and emotional learning—and external influences including the natural environment and social interactions. The movie is proven to be a valuable medium for character education, particularly for adolescents, as it aligns with the principles of the Pancasila Student Profile and supports educational efforts to instill moral and social values through engaging and relatable narratives. This study concludes that animated films like The Wild Robot can effectively contribute to character development in educational contexts.